Lusutrombopag for the Treatment of Thrombocytopenia in Patients With Chronic Liver Disease Undergoing Invasive Procedures (L‐PLUS 2). Issue 4 (15th March 2019) - Peck‐Radosavljevic, Markus; Simon, Krzysztof; Iacobellis, Angelo; Hassanein, Tarek; Kayali, Zeid; Tran, Albert; Makara, Mihaly; Ben Ari, Ziv; Braun, Marius; Mitrut, Paul; Yang, Sheng‐Shun; Akdogan, Meral; et al.
Abstract : Thrombocytopenia may be associated with increased bleeding risk impacting timing and outcome of invasive procedures in patients with chronic liver disease (CLD). Lusutrombopag, a small‐molecule, thrombopoietin (TPO) receptor agonist, was evaluated as a treatment to raise platelet counts (PCs) in patients with thrombocytopenia and CLD undergoing invasive procedures. L‐PLUS 2 was a global, phase 3, randomized, double‐blind, placebo‐controlled study. Adults with CLD and baseline PCs < 50 × 10 9 /L were randomized to receive once‐daily lusutrombopag 3 mg or placebo ≤ 7 days before an invasive procedure scheduled 2‐7 days after the last dose. The primary endpoint was avoidance of preprocedure platelet transfusion and avoidance of rescue therapy for bleeding. A key secondary endpoint was number of days PCs were ≥ 50 × 10 9 /L throughout the study. Safety analysis was performed on patients who received at least one dose of study drug. This study occurred between June 15, 2015, and April 19, 2017, with a total of 215 randomized patients (lusutrombopag, 108; placebo, 107); 64.8% (70/108) of patients in the lusutrombopag group versus 29.0% (31/107) in the placebo group met the primary endpoint ( P < 0.0001; difference of proportion 95% confidence interval [CI], 36.7 [24.9, 48.5]). The median duration of PCs ≥ 50 × 10 9 /L was 19.2 days with lusutrombopag (without platelet transfusion) compared with 0.0 in the placebo group (with platelet transfusion) ( P = 0.0001). Most adverse events were mild or moderate in severity, and rates were similar in the lusutrombopag and placebo groups (47.7% and 48.6%, respectively). Conclusion: Lusutrombopag was superior to placebo for reducing the need for platelet transfusions and achieved durable PC response in patients with thrombocytopenia and CLD undergoing invasive procedures, with a safety profile similar to placebo.